Morphology and Mechanical Properties of Poly(trimethylene terephthalate)/Maleinized Acrylonitrile-Butadiene-Styrene Blends - Bai, Yuqing; Li, Na; Liu, Yingbin; Run, Mingtao (Asian Journal of Chemistry, 2015)
Poly(trimethylene terephthalate) was melt-blended with maleinized acrylonitrile-butadiene-styrene to enhance its toughness without sacrificing comprehensive performance. The advantage of using acrylonitrile-butadiene-styrene-g-maleinized blends (ABS-g-MAH) is due to its high toughness, good processing properties and higher molecular polarity. The phase morphology, mechanical properties, crystallization behaviors, dynamic mechanical behaviors, rheology, spherulites morphology, thermal stability and thermal aging properties were investigated by scanning electron microscopy, universal tester, differential scanning calorimetry, dynamic mechanical analyzer, capillary rheometer, polarized optical microscopy, thermogravimetric analyzer and color-difference meter, respectively. The results suggest that the dimension of the dispersed phase is lower than 1 mm and the interface between acrylonitrile-butadiene-styrene and poly(trimethylene terephthalate) is not sharp. Therefore, acrylonitrile-butadiene-styrene is compatible with poly(trimethylene terephthalate) (PTT). With addition of 5 % acrylonitrile-butadiene-styrene, the yielding strength, breaking strength and impact strength of the blends increase 41.5, 167 and 200 % than those of pure poly(trimethylene terephthalate); therefore, acrylonitrile-butadiene-styrene can not only greatly toughen poly(trimethylene terephthalate) but also reinforce poly(trimethylene terephthalate) to some extent with proper additions. Acrylonitrile-butadiene-styrene also serves as a nucleating agent for increasing the crystallization rate. The blends show larger storage modulus and higher glass transition temperatures than those of pure poly(trimethylene terephthalate). Acrylonitrile-butadiene-styrene improves the processing property of poly(trimethylene terephthalate) by increasing the apparent viscosity of the blends. However, the blends of PTT/ABS show decreased thermal aging resistance of the blends.